Etoricoxib Induced Toxic Epidermal Necrolysis: A Case Report - Farooqui, Saba; Shyma, Zuha; Zulekha, Suha; Martis, Jacintha; V, Adarsh V (Indian Journal of Pharmacy Practice)
Toxic Epidermal Necrolysis (TEN) is a rare and life-threatening skin reaction that can quickly lead to dehydration and infection. TEN is perhaps the most formidable disease encountered by dermatologists, and it remains as puzzling a disorder as it was when described by Lyell. Etoricoxib is a medication that has been associated with TEN. The ideal medical management of TEN should be multidisciplinary and requires early diagnosis and withdrawal of suspected/causative drug(s), supportive care, and specific therapy. Here we present a case of Toxic Epidermal Necrolysis due to Etoricoxib in an immune-compromised patient.
Keywords: Toxic Epidermal Necrolysis; Etoricoxib; Case Report